Modelling Tribochemical Reactions of Lubricants in the UHV Analytical Tribometer - Maria Isabel De Barros-Bouchet (Japanese Society of Tribologists, 2015)
Gas Phase Lubrication (GPL) is used here to lubricate counterparts of a tribological system with a partial pressure of a gas. Because the rheological contribution (Hydrodynamic and EHL) of gas is practically negligible, the role of tribochemical reactions is of prime importance to achieve a good performance. Different sites of the contact zone are subjected to chemical reactions: inside-contact acid-base reactions, plasma-induced reactions in the vicinity of the contact area and nascent surfaces in the extended part of the worn surface. Here we highlight the interest of GPL in modeling boundary lubrication.